Southern Africa crustal anisotropy reveals coupled crust-mantle evolution for over 2 billion years - H. Thybo (Nature Portfolio, 2019)
The long-term stability of Precambrian continental lithosphere depends on the rheology of the lithospheric mantle as well as the coupling between crust and mantle lithosphere. Here, the authors study crustal seismic anisotropy to reveal that the crust and mantle lithosphere of southern Africa have been coupled since cratonisation, over 2 billion years ago.